2010
DOI: 10.1158/1078-0432.ccr-10-0825
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of High-Mobility Group Box 2 Is Associated with Tumor Aggressiveness and Prognosis of Hepatocellular Carcinoma

Abstract: Purpose: We investigated the expression of high-mobility group box 2 (HMGB2) in patients with hepatocellular carcinoma (HCC) and its clinical effects with underlying mechanisms.Experimental Design: HMGB2 mRNA levels were measured in 334 HCC patients by real-time reverse transcription-PCR and HMGB2 protein levels in 173 HCC patients by immunohistochemical studies. The HMGB2 expression level was measured by Western blotting for three HCC cell lines. To clarify the precise role of HMGB2 on cell proliferation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 37 publications
(33 reference statements)
4
83
0
Order By: Relevance
“…7,10 Reports have also highlighted the interactions of HMGB1 with TLR9, retinoic acid-inducible gene I and TIM-3 10,37,38 and the vital role of HMGBs in autophagy regulation, 39 mitochondrial function and morphology [40][41][42] and cell proliferation. [43][44][45] Comparatively, an understanding of HMGBs in the nucleus is limited. In addition to their classical functions in transcriptional regulation or their DNA-binding properties, nuclear HMGBs may assist in the replication of some viruses.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Reports have also highlighted the interactions of HMGB1 with TLR9, retinoic acid-inducible gene I and TIM-3 10,37,38 and the vital role of HMGBs in autophagy regulation, 39 mitochondrial function and morphology [40][41][42] and cell proliferation. [43][44][45] Comparatively, an understanding of HMGBs in the nucleus is limited. In addition to their classical functions in transcriptional regulation or their DNA-binding properties, nuclear HMGBs may assist in the replication of some viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In ALL, the upregulation of pseudogenes RP11-423H2.1, FAM86C2P, and HMGB1P41 was associated with the upregulation of their parent genes THOC3, FAM86A, and HMGB2. Previous studies have shown that HMGB2 is overexpressed in a variety of cancers and that there is a decline in the proliferation of cancer cells when siRNA is used to knockdown expression of HMGB2, 29,30 suggesting a putative role in the pathogenesis of ALL. Likewise, some pseudogenes were downregulated and their parent genes were also downregulated.…”
Section: Differential Expression Of Transcripts With Epigenetic Regulmentioning
confidence: 99%
“…15 In hepatocellular carcinoma, HMGB2 overexpression has been significantly correlated with shorter overall survival time. 16 Despite extensive characterization of the diverse roles of HMGB1, relatively less is known of the specific biological function of HMGB2.…”
Section: Introductionmentioning
confidence: 99%